Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Fe3O4@Polyaniline enhanced algal-bacterial symbiotic granular sludge for efficient pollutant removal under low aeration conditions - Lingfeng Ouyang; Qian Hu; Bin Qiu (Environmental Research, 2026)

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Dynamic characterization of representative naval steels under high-velocity fragment impact and functional vulnerability assessment of naval propulsion-system components - WenCai Sun; HouXiang Wang; LingFeng Hu; YuAng Shi; JianNan Li; ZiChun Yang (Ocean Engineering, 2026)

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

Nanoplastic exposure induces exoskeletal misdevelopment in juvenile Tachypleus tridentatus: Compensatory hardening versus molecular suppression - Lingfeng Jiang; Youji Wang; James Kar-Hei Fang; Khor Waiho; Wei Liu; Jae-Seong Lee; Xiaowan Ma; Menghong Hu (Marine Pollution Bulletin, 2026)

Dietary 5-aminolevulinic acid induces strain-specific effects on shell color and innate immunity in Pacific oyster (Crassostrea gigas) through divergent porphyrin metabolism - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Fish & Shellfish Immunology, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Polystyrene microplastics impede growth and induce behavioural toxicity in endangered juvenile horseshoe crabs (Tachypleus tridentatus) - Yi Jiang; Zhiyuan Yang; Lingfeng Jiang; Cheong-Meng Chong; Shanza Gul; Youji Wang; Khor Waiho; Xiaowan Ma; Zhi Chen; Menghong Hu (Marine Environmental Research, 2026)

Reproductive capacity and hereditary impact of triploid Crassostrea gigas and its aneuploid progeny - Xianchao Bai; Hong Hu; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Haijun Liu; Shaojun Du; Qi Li (Marine Life Science & Technology, 2026)

Orange-shell phenotype regulated by CgABCG2-mediated protoporphyrin IX transport in Pacific oyster (Crassostrea gigas) - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Aquaculture, 2026)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Trade winds control sedimentation on reefs and carbonate platforms: a comprehensive review - Rufei Peng; Chenlin Hu; Jonathan Atuquaye Quaye; Lirong Zhu; Lingfeng Zhao (International Geology Review, 2025)

Transcriptomic insights into an ancient and endangered species: Adverse effects of nanopolystyrene on the behavior and energy metabolism of Tachypleus tridentatus - Lingfeng Jiang; James Kar-Hei Fang; Youji Wang; Xiaowan Ma; Jae-Seong Lee; Menghong Hu (Journal of Hazardous Materials, 2025)

Discharge and deposition metallogenic model of “Datangpo-type” manganese deposits in China: Geophysical evidence from deep electrical structure of manganese-bearing grabens - Bingnan Yang; Xiangyun Hu; Lingfeng Gao; Xiaoqing Shen; Weiyang Liao; Jiajun Wang; Liangjun Yuan (Journal of Asian Earth Sciences, 2025)

Delta sedimentary evolution: a comprehensive review and perspectives on construction and destruction - Lirong Zhu; Chenlin Hu; Jonathan Atuquaye Quaye; Rufei Peng; Lingfeng Zhao (International Geology Review, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.

Machine learning-based prediction of terrestrial heat-flow across mainland China - Chang Ni; Shan Xu; Xiangyun Hu; Xianchun Tang; Wenglong Zhou; Lingfeng Gao (Tectonophysics, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

CgPPOX and CgFECH Mediate Protoporphyrin IX Accumulation Predominantly in the Outer Mantle Fold of Pacific Oyster Crassostrea gigas - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

Intelligent identification of carbonate components based on deep learning - Yuqing Dong; Chenlin Hu; Jonathan Atuquaye Quaye; Ning Lu; Lingfeng Zhao (Facies, 2025)

Paleoclimate evolution of the Middle Triassic Guanling Formation from South China and its significance for the preservation of the Luoping biota - Zhongzhao Ding; Zhixin Ma; Shixue Hu; Shuang Dai; Qiyue Zhang; Xiao Min; Jinyuan Huang; Wen Wen; Changyong Zhou; Xinnan Fang; Tianqi Ji; Lingfeng Qin (Global and Planetary Change, 2024)

Comparative analysis on growth performance, survival and harvest traits between offspring from wild and mass-selected populations of Crassostrea nippona - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Aquaculture, 2024)

Hormone and reproductive factors and risk of systemic lupus erythematosus: a Mendelian randomized study - Runyu Chang; Shate Xiang; Yibo Jin; Xiaofen Xu; Suhai Qian; Lingfeng Chen; Chao Hu; Yufeng Shi; Xinghong Ding (Immunologic Research, 2024)

Potential high-risk release sources of thallium and arsenic from surrounding rocks of a typical thallium and arsenic mining area in southwest China - Yanpei Du; Lingfeng Shi; Xinyan Cao; Fengqi Zhao; Pengjie Hu; Rongrong Ying; Shangyi Gu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Hypoxia impairs cellular energy allocation in the juvenile horseshoe crab Tachypleus tridentatus - Lingfeng Jiang; Meilian Huang; Chunhua Liu; Mohamed H. Abo-Raya; Xiaowan Ma; Youji Wang; Menghong Hu (Journal of Experimental Marine Biology and Ecology, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Impact of hypoxia on glucose metabolism and hypoxia signaling pathways in juvenile horseshoe crabs Tachypleus tridentatus - Lingfeng Jiang; Yueyong Shang; Yuntian Shi; Xiaowan Ma; Malik ShahZaib Khalid; Meilian Huang; James Kar-Hei Fang; Youji Wang; Kianann Tan; Menghong Hu (Marine Environmental Research, 2024)

Potential mobilization of water-dispersible colloidal thallium and arsenic in contaminated soils and sediments in mining areas of southwest China - Yanpei Du; Lingfeng Shi; Xinyang Li; Juan Liu; Rongrong Ying; Pengjie Hu; Longhua Wu; Peter Christie (Journal of Hazardous Materials, 2024)

Water-dispersible colloids facilitate the release of potentially toxic elements from contaminated soil under simulated long-term acid rain - Juan Liu; Lingfeng Shi; Yanpei Du; Xueting Luo; Pengjie Hu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

Photothermal microneedle patch loaded with antimicrobial peptide/MnO2 hybrid nanoparticles for chronic wound healing - Guanyi Wang; Wang Wang; Zesheng Chen; Tao Hu; Lingfeng Tu; Xiaolong Wang; Weikang Hu; Sheng Li; Zijian Wang (Chemical Engineering Journal, 2024)

Saving the overlooked mangrove horseshoe crabs-A perspective from enhancing mangrove ecosystem conservation - Yuntian Shi; Shuhui Li; Yaowu Li; Lingfeng Jiang; Fahim Ullah Khan; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Chronic exposure to IQOS results in impaired pulmonary function and lung tissue damage in mice - Jianjun Gu; Daohui Gong; Yuxiu Wang; Tingting Feng; Jun Zhang; Suwei Hu; Lingfeng Min (Toxicology Letters, 2023)

A Comparative Study on the Difference in Temperature and Salinity Tolerance of Crassostrea nippona and C. gigas Spat - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Journal of Marine Science and Engineering, 2023)
Although Crassostrea nippona and C. gigas are occasionally found to be sympatric, little is known about the differences in tolerance against environmental stresses between species, which may potentially result in severe economic losses due to the neglect of species-specific biological characteristics in farming practices. Therefore, two independent and consecutive experiments were performed to evaluate the differences in temperature and salinity tolerance between C. nippona and C. gigas spat and determine the optimal environmental conditions for the aquaculture of C. nippona spat. The experimental results of dynamic treatment showed that the accumulative survival rate (ASR) of C. nippona spat was generally lower than that of C. gigas throughout temperature changes and salinity decreases, while the ASR of C. nippona spat was superior to that of C. gigas with increasing salinity. In addition, the daily growth rate (DGR) of both species was significantly inhibited at 18 °C and peaked at 25 °C with increasing temperature (p

Correction: Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Performance of the BDS3 experimental satellite passive hydrogen maser - Ziqian Wu; Shanshi Zhou; Xiaogong Hu; Li Liu; Tao Shuai; Yonghui Xie; Chengpan Tang; Junyang Pan; Lingfeng Zhu; Zhiqiao Chang (GPS Solutions, 2018)

Multiparameter cluster analysis of seasonal variation of water masses in the eastern Beibu Gulf - Shengli Chen; Yan Li; Jianyu Hu; Airong Zheng; Lingfeng Huang; Yuanshao Lin (Journal of Oceanography, 2011)